Integrasi Prinsip Syariah dalam Pencegahan Diabetes Mellitus - Hengki Januardi; Ade Sri Wahyuni; Andy Riski Pratama; Yulia Ningsih; Rio Rahmat Yusran (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine diabetes mellitus from an Islamic spiritual perspective, as well as how the concept of a harmonious family and the teachings of the Qur'an can be implemented as part of healing and prevention efforts. This study uses a qualitative method based on libraries by examining primary and secondary sources in the form of the Qur'an, hadith, health literature, and the thoughts of scholars. The results of the study indicate that diabetes mellitus is a metabolic disorder characterized by increased blood glucose levels due to insulin disorders. From an Islamic perspective, one of the causes of this disease is excessive stress, an unbalanced diet, and a lack of self-control, all of which are forms of the physical and spiritual world. The Qur'an provides a solution through a spiritual approach such as dhikr, fasting, and honey consumption. In the context of Islamic law, maintaining health is part of maqāṣid al-syarī‘ah, especially in maintaining the soul (ḥifẓ al-nafs) and maintaining religion (ḥifẓ al-dīn), because a healthy body is needed to carry out worship perfectly. Therefore, efforts to cure and prevent diabetes through a spiritual approach are not only medical and psychological, but also a sharia obligation that has worship value. This study confirms that a holistic approach between medical, spiritual, and Islamic law can provide a positive contribution in dealing with chronic diseases such as diabetes mellitus.